Surgical approach to neglected giant cervical fibroids - Emeklioglu, Cagdas Nurettin; Aydin, Emine; Konal, Merve; Şirinoğlu, Hicran; Aktürk, Erhan; Akbayir, Ozgur (The European Research Journal, 2023)
Cervical fibroids are rare neoplasms of uterine origin whose management has not been standardized. Cervical fibroids, which can be challenging in surgical management, can become a difficult problem for the surgeon when neglected or asymptomatic and reach gigantic dimensions. Suspending the aorta abdominalis or arteria illiaca communis with vascular tapes and balloting the uterus with the help of vaginal taping while searching for the correct cleavage may reduce the risk of intraoperative hemorrhage and adjacent organ injury, as well as may be guide for the steps of the operation. Management of neglected giant cervical fibroids may not be suitable for testing alternative treatment methods to surgery used in the treatment of uterine neoplasms. However, surgical management will also be challenging. For this reason, the technique we describe can help the surgeon with clues that should be considered in the surgical management of these patients.